Interaction in acting training and its different manifestations in novice and professional actors - Sun, Jingyan; Okada, Takeshi (Frontiers in Psychology, 2023)
This study aimed to identify the characteristics of interactions during acting training and the underlying intrapersonal changes evoked by a training process that emphasizes paying attention to a partner (the Meisner technique). This was operationalized by conducting a post-hoc analysis and categorizing the utterances made by novice and professional actors during acting training based on video and audio recordings. In Study 1, novice participants tended to change their way of communication as the course progressed, decreasing the number of utterances that simply described the partner’s behavior and increasing those that speculated about the partner’s inner state. We then used a different focus placed on the interaction, as implied by the different kinds of utterances used, to describe the divergences between novice and professional actors regarding their interaction characteristics. In Study 2, results showed that while professional actors devoted themselves more to the connection with their partner and demonstrated more balanced communication, novice actors relied on general inference to speculate about others’ affective states. By comparing the characteristics of the utterances between novice and professional actors as they played different roles or made switches (i.e., changing from passive to active utterance in communication), this study suggests that an important impact of acting training on social abilities relates to its potential to increase the levels of involvement in on-going interactions.